2002
DOI: 10.1046/j.1365-2745.2002.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seed predators on the recruitment of mangroves

Abstract: Summary1 Propagule (diaspore) predation by crabs has been shown to be a major source of mortality for mangroves. We measured predation by crabs on seeds of nine tropical mangrove species in multifactorial experiments by following the fates of tethered propagules. 2 We tested whether planting, intertidal position and canopy gaps influenced predation of propagules and whether the predation of propagules was reduced in the presence of conspecifics. We also tested if predation influenced patterns of propagule esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 32 publications
4
65
3
Order By: Relevance
“…Factors know to affect these processes include: flooding depth and period (Rabinowitz 1978;Jimenez and Sauter 1991;McGuinness 1997a;Delgado et al 2001), soil characteristics (Jimenez and Sauter 1991;McKee 1995a), desiccation stress (Jimenez and Sauter 1991;McKee 1995a;McGuinness 1997a), and predation by crabs (Smith 1987;Smith et al 1989;McKee 1995b;McGuinness 1997b;Sousa and Mitchell 1999;Delgado et al 2001;Clarke and Kerrigan 2002). Two less well-studied factors that may influence the success of dispersing propagules and young seedlings are propagule size and predispersal damage by insects (Onuf et al 1977;Robertson et al 1990;Minchinton and Dalby-Ball 2001).…”
mentioning
confidence: 99%
“…Factors know to affect these processes include: flooding depth and period (Rabinowitz 1978;Jimenez and Sauter 1991;McGuinness 1997a;Delgado et al 2001), soil characteristics (Jimenez and Sauter 1991;McKee 1995a), desiccation stress (Jimenez and Sauter 1991;McKee 1995a;McGuinness 1997a), and predation by crabs (Smith 1987;Smith et al 1989;McKee 1995b;McGuinness 1997b;Sousa and Mitchell 1999;Delgado et al 2001;Clarke and Kerrigan 2002). Two less well-studied factors that may influence the success of dispersing propagules and young seedlings are propagule size and predispersal damage by insects (Onuf et al 1977;Robertson et al 1990;Minchinton and Dalby-Ball 2001).…”
mentioning
confidence: 99%
“…The high growth rates and the relative insensitivity to changes in survival and establishment of propagules and seedlings seem to indicate that mangroves' strategy of reproduction is adapted to less favourable conditions with higher losses, especially for the young growth stages. Indeed, studies have reported quite a high variability in propagule and seedling survival (Bhat et al 2004;Clarke and Kerrigan 2002;Clarke et al 2001;Hogarth 1999;Kitaya et al 2002). Given the life-history parameters in our model, reforestation should present no problem in most areas.…”
Section: Discussionmentioning
confidence: 88%
“…The influence of positive feedbacks in mangroves, however, is not dependent on the specific mechanism involved. Given that positive feedbacks have been found to be present in various systems (Scheffer et al 2001) (Clarke and Kerrigan 2002). Studying feedback mechanisms in mangroves could follow studies in other systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, field studies indicate that only a few of those hypocotyls which have fallen at the parental sites, settled well and showed further growth. Clarke and Kerrigan (2002) reported that the small-sized hypocotyls contain high nutrient content and low fibber content. The crabs prefer to consume such hypocotyls and feed on them prior to establishment.…”
Section: Floral Biologymentioning
confidence: 99%